Socioeconomic disparities in household secondhand smoke exposure among non-smoking adolescents in the Republic of Korea. Issue 9 (2nd September 2017) - Park, Sunhee; Lim, Sungwon; Kim, Junghee; Lee, Haein; June, Kyung Ja
ABSTRACT: This nationally representative study examined (a) gender and age differences in household secondhand smoke exposure (HSHSE) and (b) associations between socioeconomic status (SES) and HSHSE among non-smoking Korean adolescents. Two subsamples were analysed: males ( n = 25, 648) and females ( n = 30, 240). The HSHSE measures were incidence of HSHSE (yes/no) and number of days of HSHSE (1–7 days); the SES measures were parental education, perceived economic status, and family wealth. For the first aim, chi-square test, t -test, and bivariate negative binomial regression analysis were performed; For the second aim, multivariate logistic regression and negative binomial regression analyses were performed. The incidence and number of days of HSHSE were significantly higher among females (32.35% and 3.48 days) than males (26.83% and 3.08 days). The HSHSE incidence was significantly higher among younger adolescents (23.32% to 31.08% of males and 26.58% to 37.03% of females). Lower SES was associated with (a) greater odds of HSHSE (odds ratio: 1.12–1.58 among males and 1.19–1.85 among females) and (b) greater incidence rates of HSHSE (incidence rate ratio: 1.05–1.17 among males and 1.10–1.14 among females). Efforts should be made to decrease HSHSE among adolescents, particularly low-SES youth.